Leucine-rich alpha-2-glycoprotein 1 deficiency suppresses ischemia–reperfusion injury-induced renal fibrosis - Naohito Okami; Hiromichi Wakui; Kengo Azushima; Tomohito Miyazawa; Eisuke Kubo; Shunichiro Tsukamoto; Mari Sotozawa; Shinya Taguchi; Shingo Urate; Kohei Ishiga; Sho Kinguchi; Tomohiko Kanaoka; et al. (Scientific Reports)
Abstract Ischemia reperfusion injury (IRI) is a major cause of acute kidney injury (AKI) and ultimately leads to renal fibrosis, primarily via the transforming growth factor-β (TGF-β) pathway. Leucine-rich alpha-2-glycoprotein 1 (LRG1), a novel modulator of the TGF-β pathway, has been implicated in the modulation of renal fibrosis by affecting the TGF-β/Smad3 signaling axis. However, the role of LRG1 in the transition from AKI to chronic kidney disease (CKD) remains unclear. This study aimed to investigate the functional role of LRG1 during the remodeling phase post-IRI. Unilateral IRI was induced in C57BL/6J wild-type (WT) mice and systemic LRG1 knockout (KO) mice. In C57BL/6J WT mice, renal LRG1 mRNA expression was significantly elevated on the ischemia/reperfusion side compared to the sham side over a 28-day period. In contrast, LRG1 KO mice demonstrated significantly reduced renal fibrosis compared to WT mice on postoperative day 28. Additionally, renal mRNA expression of TGF-β and associated pro-fibrotic genes was diminished in LRG1 KO mice compared to WT mice. Consequently, LRG1 KO mice exhibited attenuated IRI-induced chronic fibrosis. These findings indicate that LRG1 is involved in the pathogenesis of the transition from AKI to CKD and may be a potential therapeutic target.